Research on Optimized Design of FPGA Parallel Processing Structure in New High-speed Signal Acquisition System - Ji, Yaozhou; Liu, Liyu (International Journal of Computer Science and Information Technology, 2025)
In the development of new high-speed signal acquisition system, it is very important to optimize the performance of parallel processing structure of FPGA. At present, the structure is faced with some difficulties, such as unreasonable resource utilization, poor module coordination and difficult balance between speed and accuracy, which limits the application and expansion of the system in communication, radar, medical imaging and other fields. In order to break through these bottlenecks, this paper conducts in-depth research. In order to improve the system performance, this paper puts forward the optimization design of resource allocation algorithm, pipelined data transmission and parallel pipelined architecture based on task load prediction. The optimized structure is realized by hardware description language coding, and the synthesis, layout and wiring are completed by professional development tools. It is verified that after optimization, the utilization rate of FPGA logic unit is increased from 52% to 85%, the average time for processing 1000 groups of data is reduced from 25.92ms to 15.58ms, the processing speed is increased by about 40.66%, and the collaborative efficiency of processing modules is significantly improved with minimal precision loss. To sum up, the optimization design proposed in this paper is practical and effective, which significantly enhances the performance of FPGA parallel processing structure and meets the growing demand of high-speed signal acquisition system.